2004
DOI: 10.3354/meps276223
|View full text |Cite
|
Sign up to set email alerts
|

Small-scale non-linear geostatistical analysis of Liocarcinus depurator (Crustacea: Brachyura) abundance and size structure in a western Mediterranean population

Abstract: The small-scale spatial distribution of density and biomass of the crab Liocarcinus depurator off the Ebro delta was analysed using universal kriging (non-linear geostatistics), considering depth as an external trend. In order to understand the spatial distribution of crab size, a third variable was created from the residuals of the non-linear regression between biomass and density. Variogram analysis of crab density and residuals of the biomass/density relationship presented a quadratic relationship with dept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 40 publications
0
20
1
Order By: Relevance
“…These species are linked more to sediment type and to the amount of suspended organic matter (Vernberg and Vernberg 1983;Rufino et al, 2004). Sediment characteristics have been found to strongly influence occurrence and distribution of many benthic decapod crustaceans, especially those with burrowing and burying habits (Atkinson and Taylor, 1988;Pinheiro et al, 1996;Comeau et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…These species are linked more to sediment type and to the amount of suspended organic matter (Vernberg and Vernberg 1983;Rufino et al, 2004). Sediment characteristics have been found to strongly influence occurrence and distribution of many benthic decapod crustaceans, especially those with burrowing and burying habits (Atkinson and Taylor, 1988;Pinheiro et al, 1996;Comeau et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…In deeper waters along the upper and middle continental slope, muddy sediments again constitute the most widespread type of sediment (Blake and Doyle, 1983). In this context, L. depurator appears to clearly favour muddy sediments over sandy or coarser sediments normally associated with higher water current velocities (Minervini et al, 1982;Rufino et al, 2004). Similar patterns of bimodal depth distribution associated with sediments with different proportions of coarse particles are found in the study areas for the distributions of burying and burrowing decapod crustaceans, such as the crabs Goneplax rhomboides, Medorippe lanata, Calappa granulata and Monodaeus couchi, the Norway lobster Nephrops norvegicus and the hermit crabs Dardanus arrosor and Pagurus prideaux (Abelló et al, 1988;Abelló et al, 2002).…”
Section: Occurrence and Densitymentioning
confidence: 99%
“…Numerous authors interpret the effective range in the exponential covariance function as a measure to describe the spatial heterogeneity or "patchiness" in a landscape (e.g., Saetre and Baath 2000;Franklin et al 2002;Schwarz et al 2003;Rufino et al 2004;Kennard and Outcalt 2006). Dalthorp et al (2000) demonstrated with discrete data that the range and nugget parameters influence the patch configuration on a simulated landscape, although Schabenberger and Gotway (2005, p. 140) questioned the use of the range parameter as an estimate of patch size.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, spatial covariance parameter estimates in ecological settings have been interpreted to describe the spatial heterogeneity or "patchiness" in a landscape that cannot be explained by measured covariates (e.g., Rossi et al 1992;Bellehumeur and Legendre 1998;Dalthorp et al 2000;Augustine and Frank 2001;Schwarz et al 2003;Rufino et al 2004;Kennard and Outcalt 2006).…”
Section: Introductionmentioning
confidence: 99%